Residence Time Distribution of Particles in a Screw Feeder: Experimental and Modelling Study. (15th July 2015) - Huo, Chaofei; Fan, Chuigang; Feng, Ping; Lin, Weigang; Song, Wenli
<x xml:space="preserve">Abstract</x> Experiments were conducted to investigate the effects of screw speed and screw feeder inclination on the residence time distribution (RTD) of particles in a screw feeder via a pulse stimulus response technique. Two models based on Markov chains were developed to simulate particle flows within and between pitches. In upward and horizontal screw feeder inclination cases, a three‐parameter two‐dimensional Markov chain model consisting of parallel active and stagnant zones fitted well with the experimental RTD data, with correlation coefficients (R2) higher than 0.98, and gave a clear physical meaning for the parameters introduced. In these cases, a high screw speed or a horizontal inclination induced a high probability of forward movement from a pitch to the next pitch (f) during each rotation period of the screw, and a low ratio of stagnant zone to active zone (r) in a pitch. The upward screw feeder inclination yielded a higher diffusion probability from stagnant zone to active zone (d). In the downward screw feeder inclination case, a one‐dimensional Markov chain model without a stagnant zone was in agreement with the corresponding experimental data. The analysis showed that during each rotation period of the screw, the particles in a pitch could be transferred not only to the next pitch but also to the following two pitches.